2017
DOI: 10.5812/asjsm.14429
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Knowledge of Lebanese Coaches: A Unique Study in the Middle East and North African (MENA) Region

Abstract: Background: Trainers provide nutritional information to their athletes, yet, their skills in this field remain weak. No related research has been conducted so far in the Middle East and North Africa (MENA) region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…ese findings are in line with the study by Salami et al in which supplement users reported having experienced one or more adverse events of supplementation including hypertension, polyuria, mood swings, and excess facial hair but still choose to consume it [30,41].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…ese findings are in line with the study by Salami et al in which supplement users reported having experienced one or more adverse events of supplementation including hypertension, polyuria, mood swings, and excess facial hair but still choose to consume it [30,41].…”
Section: Discussionsupporting
confidence: 89%
“…A recent study concluded that the Lebanese coaches and athletic trainers were not sufficiently ready to deliver quality information about sports nutrition and reported that only 26.5% of trainers have undergone formal nutrition training. ey obtain sports nutrition information mainly via the Internet and magazines [41]. Furthermore, any additional cost to gym membership fees may discourage PSU to request a sports nutrition dietitian consultation.…”
Section: Discussionmentioning
confidence: 99%
“…In Lebanon, studies on NK and athletes’ performance are very limited (Salami et al , 2017; Boumosleh et al , 2020). To date, there are no published data on NK of university student-athletes with reference to performance.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, however, it appears that athletes across various regions including the North America [ 14 , 15 ], Australia [ 6 , 7 , 13 ], New Zealand [ 16 ], Iran [ 11 ], Turkey [ 17 ], the UK [ 18 ], Ethiopioa [ 19 ], and Croatia [ 13 ] have significant gaps in their NK. Likewise, there appears to be room for improvement in the knowledge of athletic coaches across America [ 14 , 20 ] and Lebanon [ 21 ]. To our knowledge, no studies have been conducted on the NK of athletes or coaches in Jordananian society.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies conducted in non-English speaking countries rely on adapted versions of English tools but few report on the translation process and whether re-validation was undertaken. Studies in Arabic-speaking athletes have utilised modified versions of existing tools originally developed in 2003 or self-developed tools [ 17 ], and a study in Arabic-speaking coaches used a modified version of a Sports Nutrition Knowledge Questionnaire, developed in 2005 [ 21 ]. Overall, the NK questionnaires used in Arabic athletes and coaches have either been poorly validated or are not based on current sports nutrition guidelines.…”
Section: Introductionmentioning
confidence: 99%